Financial Literacy, Risk and Usefulness Perception Toward Interest in Transaction for Culinary MSMEs through Fintech in Jambi City - R, Mandasari; R, Mardiana (PT Aksara Indo Rajawali, 2024)
Nowadays, traditional business processes have been disrupted due to the Internet's involvement. Many business owners in the culinary industry now accept cashless payments from their customers, which has been impacted by the Internet's inclusion into traditional business methods like financial technology (fintech), or the automation of payment processes. Fintech can accelerate the business of small and medium-sized enterprises and create major innovation for both the owners and customers. This study aims to examine the effect of financial literacy, perception of usefulness, and risk perception on interest in using financial technology for culinary business owners. Online and offline questionnaires were distributed to 135 respondents and analyzed with SPSS statistics. Then, it was found that financial literacy and perception of usefulness significantly influence owners' interest in using fintech. Meanwhile, the risk perception does not affect owners' interest in using fintech. At the same time, financial literacy, usefulness perception, and risk perception simultaneously influence owners' interest in using fintech.